The Nucleotide-Free State of the Cannabinoid CB2/Gi Complex - Lynch, Diane L; Hurst, Dow P; Reggio, Patricia H (Cell, 2020)
In this issue of Cell, two papers report agonist-bound cryo-EM structures of the cannabinoid receptor, CB2, in complex with Gi. Importantly, beyond providing information that could help distinguish CB2 ligand binding from CB1, these structures support the existence of a nucleotide-free state during G-protein signaling.